Spontaneous rupture of right gastroepiploic artery aneurysm: a rare cause of hemorrhagic shock. Case report - Sarigoz, Talha; Carkit, Sedat; Topuz, Omer; Ertan, Tamer; Koc, Ali (São Paulo Medical Journal, 2018)
CONTEXT: Aneurysms of the gastroepiploic arteries are seen only rarely. They are usually diagnosed du- ring autopsy or laparotomy in patients with hemodynamic instability. Although the operation to treat this condition is relatively easy, delay in making the diagnosis affects the course of the disease. CASE REPORT: A 57-year-old woman was admitted to the emergency department with abdominal pain and unconsciousness. A computed tomography scan showed extravasation of contrast agent at the head- corpus junction of the pancreas, and the patient underwent exploratory laparotomy under general anes- thesia. During laparotomy, aneurysmatic rupture of the right gastroepiploic artery was detected. Control over bleeding was achieved by ligating the right gastroepiploic artery at its origin. The aneurysm was also resected and sent for pathological examination. CONCLUSION: Especially in cases of unidentified shock, splanchnic artery aneurysms should be kept in mind. Moreover, in the light of the data in the literature, the possibility of death should be taken into ac- count seriously and, if feasible, prophylactic aneurysmectomy should be performed.